APPRAISING ALIGNMENT BETWEEN SINGLE NATIONAL CURRICULUM MATHEMATICS 2020 STANDARDS AND PUNJAB EXAMINATION COMMISSION ASSESSMENT 2023 (Contemporary Journal of Social Science Review, 2025)
The Single National Curriculum (SNC) mathematics 2020 was framed to unify academic standards and promote critical thinking and cognitive rigor in mathematics. The current study was designed to measure the degree of alignment between the SNC 2020 mathematics and the Punjab Examination Commission (PEC) assessment 2023-2024, using Webb’s Alignment Tool Second Version (WAT V2). The study was a descriptive quantitative content analysis. The data sources of the study were the SNC mathematics 8th-grade document, the PEC test 2023, and six reviewers. WAT V2 was used to measure alignment between mathematics curriculum standards and assessments. The results of the study declared that standard numbers and operations comprised 23.7% and algebra 15.52%, while the standard measurement, geometry, and statistics & probability were not tested. Only 33(48.5%) SLOs were targeted, while 35(51.5%) SLOs were not targeted in the PEC assessment 2023. Depth-of-knowledge (DOK) framework comprises four levels. The DOK level-1 comprised of 4(5.88%), level-2, 22(32.4%), level-3, 42(61.7%), level-4, 0(0%) in mathematics. The results depicted less focus on DOK levels-1, Recall, and level-4 strategic thinking during the development test in mathematics. On the basis of the results of the study, it was recommended that assessment developers focus on DOK level-1, and level-4 during framing assessment items. During the decision-making, the test items PEC assessment framework may be followed for whole curriculum content coverage to ensure balanced representation in the assessment.